Capacidades de pensamento crítico : construção e validação de um instrumento de avaliação - Santana, Driane Anne Silva de (2019)
The development of critical thinking capacities has been evidenced in different official documents in the teaching of natural sciences. This research is exploratory-descriptive in nature with a multi-method approach that aims to build and validate an instrument to evaluate critical thinking abilities in high school students. The construction of the items was based on the structure of Cornell's Critical Thinking Test (Level X) and Ennis's (1985) theoretical critical thinking framework, mainly the taxonomy developed by him to construct the questions. The instrument consisted of 20 items, grouped into five domains or areas of critical thinking capacity: induction, deduction, observation, credibility and assumptions. The critical thinking test (TPC) underwent two validations, one external (students and expert judges) and the other internal (factorial analysis and internal consistency). In this complex validation process the TPC was administered twice (pilot and collective version) used to evaluate the development of critical thinking skills in a total sample of 372 students from the first and third grade of the Aracaju-Sergipe High School. The internal consistency of the domains estimated by Cronbach's alpha ranged from 0.527 in the pilot version to 0.546 when administered collectively. The factorial analysis confirmed the conceptual model and the proposed domains, but showed the need to allocate some items and rename the domains. The test indicated that in the sample of students who participated in the research there are manifestations of critical thinking abilities only in the area of assumptions. The results of the statistical analyzes showed that it is a complex process that requires the understanding of those who analyze, besides that the instrument shows that it must be reformulated and more items must be added.